Efeitos da recuperação nutricional com dieta à base de okara sobre o metabolismo hepático de lipídeos em ratos submetidos à restrição protéica na vida intrauterina e na lactação - Almeida, Ana Paula Carli de (2013)
The okara is a byproduct of the industrialization of the aqueous extract of soybean and its indication for use in human food is based on its high fiber content, high biological value proteins, bioactive components derived from soybeans and several beneficial effects on obesity prevention, hepatic steatosis and lipid disorders assessed in experimental models. The animal model of metabolic programming suggests that nutritional restrictions during critical phases of development generate able adaptations to program the metabolism in order to maintain intracellular homeostasis. These metabolic changes are strongly associated with the development of chronic diseases in adults. Our objective was to evaluate the effects okara diet in nutritional recovery of malnourished rats cat critical stages of development on hormonal, biochemical and molecular factors involved in hepatic lipid metabolism. Male rats whose mothers were fed diets with 17% or 6% of the casein-based protein during pregnancy and lactation were divided into 5 groups and maintained on diet of 17% casein (CC, LC), 17% okara (CO, LO) or 6% casein diet (LL) after weaning. Food intake and weight gain were recorded and serum glucose, insulin, and free fat acids were determined. A fraction of the liver was collected for determination of protein content and gene expression of enzymes involved on the lipid metabolism. Animals fed okara showed similar relative intake to the other groups and despite having consumed more lipids, CO and LO groups had lower body weight compared to CC and LC. The hepatic lipid content was similar between LC and LO and smaller than LL. Consumption of okara modulates negatively the gene expression of SCD1, ACC1, ACC2 and ACLY, and these results, may in part, have been modulated by higher AMPK gene expression by the CO and LO groups. Thus, the okara diet was able to modulate lipogenic genes, resulting in a protective effect on the liver in the nutritional recovery of malnourished rats previously.